Assessing Research Impact in Indian Conference Proceedings: Insights from Collaboration and Citations - Sharma, Kiran; Khurana, Parul (Journal of Data Science, Informetrics, and Citation Studies)
Conferences serve as a crucial avenue for scientific communication. However, the increase in conferences and the subsequent publication of proceedings have prompted inquiries regarding the research quality being showcased at such events. This investigation delves into the conference publications indexed by Springer’s Lecture Notes in Networks and Systems Series. Among the 570 international conferences held worldwide in this series, 177 were exclusively hosted in India. These 177 conferences collectively published 11,066 papers as conference proceedings. All these publications, along with conference details, were sourced from the Scopus database. The study aims to evaluate the research impact of these conference proceedings and identify the primary contributors. The results reveal a downward trend in the average number of citations per year. The collective average citation for all publications is 1.01. Papers co-authored by Indian and international authors (5.6%) exhibit a higher average impact of 1.44, in contrast to those authored solely by Indian authors (84.9%), which have an average impact of 0.97. Notably, Indian-collaborated papers, among the largest contributors, predominantly originate from private colleges and universities. Only 19% of papers exhibit collaboration with institutes of different prestige, yet their impact is considerably higher as compared to collaboration with institutes of similar prestige. This study highlights the importance of improving research quality in academic forums.
Keywords: Conference Publications; Research Impact; Institutional Collaboration; International Participation; LNNS.